STRATEGI PEMASARAN MELALUI MEDIA ONLINE UNTUK MENGEMBANGKAN USAHA RUMAHAN - Karen Ainiyya; Isfandayani Isfandayani; Ria Marginingsih (Universitas Islam 45 Bekasi, 2022)
Marketing strategies through online media are very important for business people, in the current era that already has increasingly advanced technology. the purpose of doing community service is so that the community can develop their business in terms of marketing through online media. Therefore, it is necessary to implement the following: (1) explain and provide marketing training through online media so that it is more widespread (2) create a home-based business product label design to make it more attractive (3) create educational content for home-based business actors so that others can find out about marketing through online media.